Bond Strength of Concrete Containing Crumb Rubber as Partial Replacement to Fine Aggregate - Mohd Azmi, Aqilah (Universiti Teknologi PETRONAS, 2017)
Crumb rubber is a recycled rubber from the scrap tires. There are environmental problem associated with waste tires. This is because the tires are bulky and non-biodegradable. The smoke released by tires that caught fire are also extremely dangerous which is difficult to extinguish and release a lot of toxic gases. Rubbercrete is a concrete containing crumb rubber as the partial replacement of fine aggregate. It is a good idea to introduce crumb rubber in concrete as it can solve the problem of the abundance of waste tire to be disposed and lack of natural fine aggregate. The advantages of using rubbercrete such as lighter in weight, high impact of resistance and better electrical resistivity. Rubbercrete also is good in ductility compare to normal concrete which is known as brittle material. However, as the percentage of crumb rubber increase the strength of rubbercrete decrease. This research paper, study about the compressive strength and bonding strength of the rubberrcrete. Thirty trial mixtures with the different percentage of crumb rubber, nano silica and fly ash were prepared. The 0%, 15% and 30% of crumb rubber replacement to fine aggregate by volume.